2020
DOI: 10.1186/s12889-020-09475-x
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence, occupational stressors, and mental health among Japanese high school teachers in Nagasaki prefecture: a multiple regression analysis

Abstract: Background International research has indicated that teachers have an increased risk of mental disorders and work-related stress, compared with those working in other fields. In Japan, the deterioration of teachers’ mental health has recently become a serious social issue. Teaching is a high-stress occupation, and job stress can affect teachers’ physical and mental health. This study aimed to determine how sense of coherence, job satisfaction, and workplace social support contribute to the mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
4
22
0
3
Order By: Relevance
“…The history of research on teacher stress is long, and studies have been reported in many countries [ 2 , 25 , 26 ]. In Japan, significant correlations were found between workload and depressive symptoms [ 10 ], workload stress and mental health [ 11 ], and both quantitative and qualitative workload and chronic fatigue [ 14 ]. These studies indicated that Japanese school teachers experienced high levels of stress in the workplace, which was detrimental to their physical and mental health, but their results seemed difficult to generalize because they were based on a survey of teachers working in schools in geographically limited region or city.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The history of research on teacher stress is long, and studies have been reported in many countries [ 2 , 25 , 26 ]. In Japan, significant correlations were found between workload and depressive symptoms [ 10 ], workload stress and mental health [ 11 ], and both quantitative and qualitative workload and chronic fatigue [ 14 ]. These studies indicated that Japanese school teachers experienced high levels of stress in the workplace, which was detrimental to their physical and mental health, but their results seemed difficult to generalize because they were based on a survey of teachers working in schools in geographically limited region or city.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Japan, the percentage of school teachers taking leave due to mental illness among all teachers has increased more than fivefold from 0.11% in 1992 to 0.59% in 2018 [ 8 , 9 ]. Existing studies found significant association between occupational stress and mental health [ 10 , 11 ], long working hours and psychological distress [ 12 ], poor mental health and lower job satisfaction [ 13 ], and prolonged fatigue and both quantitative and qualitative workload [ 14 ], among school teachers in Japan. A recent large-scale survey conducted by the Ministry of Education, Culture, Sports, Science and Technology (MEXT) found significant correlation between work hours of teachers and student-teacher ratios [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mental workload has long been a factor of immense interest in designing and applying complex human–machine systems [ 1 ], and is increasingly recognized as a serious, worldwide public health concern. Only when the mental workload is in the appropriate range can high performance and operational reliability be maintained.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, several studies indicated how stress or anxiety levels were higher than expected among teachers in the different educational levels [ 17 , 31 , 32 ]. This prevalence was represented as emotional tiredness, fatigue, headaches, sleep problems, eating or appetite alterations or disorders, irritability, exasperation, depressing feelings, or inability to focus [ 17 , 31 , 32 ]. One factor contributing to these emotional and mental issues is the technology or the information and communication technologies (ICTs), an external stressor [ 33 ].…”
Section: Introductionmentioning
confidence: 99%